Seed Dispersal by Primates and Implications for the Conservation of a Biodiversity Hotspot, the Atlantic Forest of South America - Bufalo, Felipe Soares [UNESP]; Galetti, Mauro [UNESP]; Culot, Laurence [UNESP] (Springer Nature, 2016)
Primates play a fundamental role as seed dispersers, particularly in tropical rainforests. Because defaunation and fragmentation are leading several primate species to local extinction, it is fundamental to understand the role of primates as effective seed dispersers. Here we present a systematic review of studies of seed dispersal by primates in a biodiversity hotspot, the Atlantic Forest of South America, to 1) highlight gaps in our knowledge, 2) determine species richness and proportion of seed species dispersed, and 3) test the relationship between primate body size and the size of dispersed species. Our review found 79 studies of the diet of six ecospecies (Callithrix, Leontopithecus, Callicebus, Sapajus, Alouatta, Brachyteles) but only 20 of these report information on seed dispersal, and none of these are on Callithrix or Callicebus. We found a strong bias in the distribution of species and regions, with most of the studies concentrated in southeastern Brazil. All ecospecies dispersed a large proportion of the seed species they handled (72.1–93.6%). Brachyteles dispersed the highest diversity of plants (N = 73), followed by Sapajus (N = 66), Leontopithecus (N = 49), and Alouatta (N = 26). Although we found no significant relationship between primate body size and the size of seeds dispersed, Brachyteles disperse a higher diversity of large-seeded species than smaller-bodied primates. These results suggest that the local extinction of large primate species may lead to dramatic changes in the plant community, as many large-seeded plants are inaccessible to smaller arboreal frugivores. We propose guidelines for future research on primate seed dispersal to enable the evaluation of seed dispersal effectiveness and to improve our understanding of the fundamental role of primates in this key ecosystem process.
Keywords: Defaunation; Ecosystem services; Primate conservation; Seed dispersal effectiveness; Seed dispersal network